Edukasi Enterpreneurship dalam Mengembangkan Soft Skill Siswa-Siswi SMU Negeri 14 Medan - Yanny, Anda; Hutabarat, Sumiaty Adelina (Cattleya Darmaya Fortuna, 2024)
Referring to the results of interviews with the community service partner team, there is low interest and attraction among female students for entrepreneurship and they also have to explore the soft skills they have so that when they graduate they can easily enter society for entrepreneurship. So we created a community service activity with the theme Entrepreneurship Education in developing the soft skills of students at SMU Negeri 14 Medan. This activity was carried out using two methods, namely lectures and training. The activity that we carried out received a good response from the participants, namely class XII students. They understand the material we present. The activities we carried out began by holding a test answering several multiple choice questions and at the end of the event we also carried out a test to measure the extent to which they understood the material we provided. The results we obtained were that almost 80 percent of the students understood the material regarding the basics of entrepreneurship. The games we created in groups further explored the potential of their soft skills.